2009
DOI: 10.1093/jb/mvp049
|View full text |Cite
|
Sign up to set email alerts
|

Placenta Expressing the Greatest Quantity of Bisphenol A Receptor ERR  among the Human Reproductive Tissues: Predominant Expression of Type-1 ERR  Isoform

Abstract: Estrogen-related receptor gamma (ERRgamma), one of the 48 human nuclear receptors, has a fully active conformation with no ligand. We recently demonstrated that ERRgamma binds strongly bisphenol A (BPA), one of the nastiest endocrine disruptors, and thus retaining ERRgamma's high basal constitutive activity. A report that BPA accumulates in the human maternal-fetal placental unit has led us to hypothesize that a large amount of ERRgamma might exist in the human placenta. Here we report evidence that placenta i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(44 citation statements)
references
References 26 publications
2
42
0
Order By: Relevance
“…Therefore, our results suggest that BPA has the potential to suppress normal apoptosis in embryonic hypothalamic cells and are in line with the findings of Negishi et al (24), who reported that BPA significantly inhibited Casp3 activity in foetal rat neurons treated with staurosporine, an inducer of apoptosis. Given that our highest dose of BPA decreased the expression of Casp3 and Trp73 and increased the expression of Ngf, which supports the survival and maintenance of neurons in the brain during embryonic development (25), we assume that Matsushima et al (26) have reported that BPA binds strongly to ERRγ, a receptor highly expressed in the placenta (27), which suggests that BPA has a high potential for accumulating in the placental tissue. In our study, Errγ mRNA expression gradually started to decrease from 100 µmol L -1 BPA only to reach significant reduction at 200 µmol L -1 ( Figure 4).…”
Section: The Data Have Been Normalised To the Gapdh Mrna Level In Eacsupporting
confidence: 64%
“…Therefore, our results suggest that BPA has the potential to suppress normal apoptosis in embryonic hypothalamic cells and are in line with the findings of Negishi et al (24), who reported that BPA significantly inhibited Casp3 activity in foetal rat neurons treated with staurosporine, an inducer of apoptosis. Given that our highest dose of BPA decreased the expression of Casp3 and Trp73 and increased the expression of Ngf, which supports the survival and maintenance of neurons in the brain during embryonic development (25), we assume that Matsushima et al (26) have reported that BPA binds strongly to ERRγ, a receptor highly expressed in the placenta (27), which suggests that BPA has a high potential for accumulating in the placental tissue. In our study, Errγ mRNA expression gradually started to decrease from 100 µmol L -1 BPA only to reach significant reduction at 200 µmol L -1 ( Figure 4).…”
Section: The Data Have Been Normalised To the Gapdh Mrna Level In Eacsupporting
confidence: 64%
“…ERRgamma is present in the developing embryo and neonate, and therefore could be responsible for some of BPA's actions during development. ERRgamma is also highly expressed in the placenta and it has been suggested that it may promote accumulation of BPA in the placenta and facilitate exposure of the developing fetus to this compound [82]. A recent study has confirmed elevation of ERRgamma expression in several organs of fetuses and neonates of mothers exposed to 20 g BPA/kg BW/day by oral gavage from gestational day 13 through gestational day 16 [9].…”
Section: Bpa Binds Estrogen Related Receptor Gammamentioning
confidence: 97%
“…Rabbit polyclonal anti-aromatase antibody was kindly provided by Prof. Nobuhiro Harada (Department of Biochemistry, Fujita Health University School of Medicine, Aichi, Japan) [22]. The rabbit polyclonal anti-ESRRG antibody used in the present study was established and characterized as previously reported [23]. The mouse monoclonal anti-Ran antibody (Santa Cruz Biotechnology, Inc.) was used to detect nucleus in cells.…”
Section: Immunocytochemical Stainingmentioning
confidence: 99%